The association between multimorbidity and mobility disability-free life expectancy in adults aged 85 years and over: A modelling study in the Newcastle 85+ cohort. - Laurie E Davies; Stewart W Mercer; Katie Brittain; Carol Jagger; Louise Robinson; Andrew Kingston (PLoS Medicine)
Background Mobility disability is predictive of further functional decline and can itself compromise older people's capacity (and preference) to live independently. The world's population is also ageing, and multimorbidity is the norm in those aged ≥85. What is unclear in this age group, is the influence of multimorbidity on (a) transitions in mobility disability and (b) mobility disability-free life expectancy (mobDFLE). Methods and findings Using multistate modelling in an inception cohort of 714 85-year-olds followed over a 10-year period (aged 85 in 2006 to 95 in 2016), we investigated the association between increasing numbers of long-term conditions and (1) mobility disability incidence, (2) recovery from mobility disability and (3) death, and then explored how this shaped the remaining life expectancy free from mobility disability at age 85. Models were adjusted for age, sex, disease group count, BMI and education. We defined mobility disability based on participants' self-reported ability to get around the house, go up and down stairs/steps, and walk at least 400 yards; participants were defined as having mobility disability if, for one or more these activities, they had any difficulty with them or could not perform them. Data were drawn from the Newcastle 85+ Study: a longitudinal population-based cohort study that recruited community-dwelling and institutionalised individuals from Newcastle upon Tyne and North Tyneside general practices. We observed that each additional disease was associated with a 16% increased risk of incident mobility disability (hazard ratio (HR) 1.16, 95% confidence interval (CI): 1.07 to 1.25, p < 0.001), a 26% decrease in the chance of recovery from this state (HR 0.74, 95% CI: 0.63 to 0.86, p < 0.001), and a 12% increased risk of death with mobility disability (HR: 1.12, 95% CI: 1.07- to .17, p < 0.001). This translated to reductions in mobDFLE with increasing numbers of long-term conditions. However, residual and unmeasured confounding cannot be excluded from these analyses, and there may have been unobserved transitions to/from mobility disability between interviews and prior to death. Conclusions We suggest 2 implications from this work. (1) Our findings support calls for a greater focus on the prevention of multimorbidity as populations age. (2) As more time spent with mobility disability could potentially lead to greater care needs, maintaining independence with increasing age should also be a key focus for health/social care and reablement services.